2017
DOI: 10.3791/55222
|View full text |Cite
|
Sign up to set email alerts
|

Human Lung Dendritic Cells: Spatial Distribution and Phenotypic Identification in Endobronchial Biopsies Using Immunohistochemistry and Flow Cytometry

Abstract: The lungs are constantly exposed to the external environment, which in addition to harmless particles, also contains pathogens, allergens, and toxins. In order to maintain tolerance or to induce an immune response, the immune system must appropriately handle inhaled antigens. Lung dendritic cells (DCs) are essential in maintaining a delicate balance to initiate immunity when required without causing collateral damage to the lungs due to an exaggerated inflammatory response. While there is a detailed understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Additionally, DCs expressing CD1a can be detected in both the epithelium and submucosa of the airways (117, 118, 122). More detailed phenotypic analyses revealed that a subpopulation of CD1c + MDCs express CD1a, mannose receptor (CD206) and langerin (CD207) in human lungs, unlike blood CD1c + MDCs (62, 73, 74, 123).…”
Section: Phenotypic and Functional Characterization Of Human Lung Mnpsmentioning
confidence: 99%
“…Additionally, DCs expressing CD1a can be detected in both the epithelium and submucosa of the airways (117, 118, 122). More detailed phenotypic analyses revealed that a subpopulation of CD1c + MDCs express CD1a, mannose receptor (CD206) and langerin (CD207) in human lungs, unlike blood CD1c + MDCs (62, 73, 74, 123).…”
Section: Phenotypic and Functional Characterization Of Human Lung Mnpsmentioning
confidence: 99%
“…As T cells are critical in driving disease progression in sarcoidosis, a more detailed understanding of MNPs that initially activate and modulate T cell responses could provide greater insight on sarcoidosis pathogenesis. We recently developed protocols and characterized MNPs in healthy controls and identified classical, intermediate, and non‐classical monocytes distinguished by their differential expression of CD14 and CD16 as well as CD123 + plasmacytoid DCs (PDCs) and CD1c + and CD141 + myeloid DCs (MDCs) in the respiratory tract . The different subsets of DCs and monocytes have common but also unique features .…”
Section: Introductionmentioning
confidence: 99%
“…1 Sarcoidosis can present with either an acute onset (usually Löfgren's syndrome (LS)) associated with more favorable disease outcome or a Abbreviations: BAL, bronchoalveolar lavage; DC, dendritic cell; EBB, endobronchial biopsy; EBUS-TBNA, endobronchial ultrasound-guided transbronchial needle aspiration; LLN, lung-draining lymph node; MNP, mononuclear phagocyte protocols and characterized MNPs in healthy controls and identified classical, intermediate, and non-classical monocytes distinguished by their differential expression of CD14 and CD16 as well as CD123 + plasmacytoid DCs (PDCs) and CD1c + and CD141 + myeloid DCs (MDCs) in the respiratory tract. 5,6 The different subsets of DCs and monocytes have common but also unique features. 7 Classical monocytes circulate in blood and either extravasate into tissues or differentiate into intermediate monocytes and non-classical monocytes.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have generated important insight in this area and Mϕs, monocytes, monocyte-derived DCs (mo-DCs), and bona fide DC subsets have been identified from healthy human respiratory tissues. Figure 1 summarizes the current understanding of the phenotype and distribution of human MNP subsets in respiratory tissues at steady state, as reported ( 41 , 51 , 52 , 57 62 ).…”
Section: Human Respiratory Mnpsmentioning
confidence: 94%
“…(B) Distribution of human MNP subsets. Pie charts illustrate broadly pooled data from 21 published studies on human MNP subset distribution in blood, tonsils, BAL, and lung tissue to demonstrate the differential distribution of MNPs across anatomical compartments reported from many research groups ( 51 , 52 , 57 61 , 63 76 ). As different studies utilize different strategies to specifically define MNPs, the pie charts show groups of cells typically including several subsets of cells: Mϕs (beige), monocytes (green), myeloid DCs (MDCs) (coral), and plasmacytoid DCs (PDCs) (teal).…”
Section: Human Respiratory Mnpsmentioning
confidence: 99%